Autoinflammatory diseases: the hereditary periodic fever syndromes - Fietta, P. (Acta Biomedica Atenei Parmensis, 2004)
Human autoinflammatory diseases (HAIDs) are a heterogeneous group of genetically determined affections characterized by seemingly unprovoked inflammation, in the absence of autoimmune or infective causes. The hereditary periodic fever syndromes (HPFSs) are a HAID subset consisting of three main nosologic entities: familial Mediterranean fever (FMF), hyperimmunoglobulinemia D and periodic fever syndrome (HIDS), and tumor necrosis factor receptor superfamily 1A-associated periodic syndrome (TRAPS). FMF and HIDS are autosomal recessive diseases, while TRAPS is dominantly inherited. Although each HPFS presents genetic and phenotypic peculiarities, globally these affections share an intermittent expression, in form of acute attacks of fever variably associated with serosal, synovial and/or cutaneous inflammation, usually self-limiting. Amyloidosis is the most severe, life-threatening complication of FMF and TRAPS, whereas it has not been till now reported in HIDS. The HPFS molecular bases have been recently identified. In this paper, the most recent information on HPFSs is reviewed and summarized.